2021
DOI: 10.1080/14613808.2021.1906215
|View full text |Cite
|
Sign up to set email alerts
|

The worst is yet to come: the psychological impact of COVID-19 on Hong Kong music teachers

Abstract: The worst is yet to come: The psychological impact of COVID-19 on Hong Kong music teachersThe COVID-19 pandemic has made online and distance learning the new normal at all levels of education. Music as a school subject that relies heavily on multimodal sensory and auditory-motor interactions has been dramatically affected. Music teachers may not be coping mentally or psychologically with these drastic changes. This study examined the psychological impact of COVID-19 on music teachers' (N = 120) mental health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 39 publications
4
58
1
3
Order By: Relevance
“…In addition, 77% of these music teachers reported at least some level of Depression, with nearly a quarter (24%) of their scores falling into the severe or extremely severe classifications. Clearly, these music teachers were struggling and this is supported by the findings in emerging research (e.g., Cornett, 2020 ; Cheng and Lam 2021 ).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In addition, 77% of these music teachers reported at least some level of Depression, with nearly a quarter (24%) of their scores falling into the severe or extremely severe classifications. Clearly, these music teachers were struggling and this is supported by the findings in emerging research (e.g., Cornett, 2020 ; Cheng and Lam 2021 ).…”
Section: Discussionmentioning
confidence: 74%
“…The well-being of music teachers in the United States has been examined with this model (Miksza et al, 2021;Parkes et al, 2021), and the findings indicated significantly lower levels of overall well-being, in addition to significantly higher levels of depression than published norms. Cheng and Lam (2021) studied the well-being of music teachers in Hong Kong. Some of the teachers (n = 20) in their sample were interviewed, whereas others (n = 120) completed a survey which included a Fear of Coronavirus-19 Scale, a Generalized Anxiety Disorder Scale, and a Chinese Teacher Stress Questionnaire (short form).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Teaching is generally considered a highly stressful profession ( Harmsen et al, 2018 ), and the COVID-19 crisis has made things even worse ( Kumawat, 2020 ). Online teaching had a negative psychological impact on teachers, causing them to feel anxious, stressed, and depressed ( Cheng and Lam, 2021 ; Ozamiz-Etxebarria et al, 2021 ). Pressley (2021a) found that the antecedents to teacher burnout-stress were COVID-19 anxiety, current teaching anxiety, anxiety communicating with parents, and lack of administrative support.…”
Section: Introductionmentioning
confidence: 99%